2007
DOI: 10.1038/ncb1654
|View full text |Cite
|
Sign up to set email alerts
|

Filopodia are required for cortical neurite initiation

Abstract: Extension of neurites from a cell body is essential to form a functional nervous system; however, the mechanisms underlying neuritogenesis are poorly understood. Ena/VASP proteins regulate actin dynamics and modulate elaboration of cellular protrusions. We recently reported that cortical axon-tract formation is lost in Ena/VASP-null mice and Ena/VASP-null cortical neurons lack filopodia and fail to elaborate neurites. Here, we report that neuritogenesis in Ena/VASP-null neurons can be rescued by restoring filo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
343
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(371 citation statements)
references
References 50 publications
26
343
2
Order By: Relevance
“…In addition to the regulation of spine morphogenesis, mDia2/DFR3 has a significant role in neurite extension 81 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition to the regulation of spine morphogenesis, mDia2/DFR3 has a significant role in neurite extension 81 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As for the role of the actin cytoskeleton, although earlier work suggested that the actin depolymerizing drug cytochalasin D did not inhibit neurite formation in chick dorsal root ganglia neurons [40], more recent studies have demonstrated a critical role of the Ena/Mena/VASP family of proteins (abbreviated as Ena/VASP) in neurite formation [41,42]. Ena/VASP proteins regulate actin dynamics by antagonizing actin filament capping and promoting filament bundling [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Ena/VASP proteins regulate actin dynamics by antagonizing actin filament capping and promoting filament bundling [43,44]. In mice lacking all three Ena/VASP proteins, cortical neurons lacked filopodia and failed to initiate neurites, a process that can be rescued either by over-expression of the actin nucleating protein mDia2 or by plating neurons on the filopodia-promoting laminin substrate [41]. In another recent study, the actin depolarizing factor (ADF)/Cofilin family, which depolymerizes and severs actin filaments [45,46], was shown to promote neurite formation by driving actin retrograde flow and thereby allowing microtubule protrusion [47].…”
Section: Introductionmentioning
confidence: 99%
“…Neuritic sprouting starts at actin‐rich filopodial protrusions (Dent et al. 2007). To test whether the WIP contribution to neuron complexity was linked to this very early event, we quantified the number of neuritic filopodia and F‐actin patches (transient accumulations of F‐actin within the neuritic shaft which serve as precursors for neuritic filopodia [Loudon et al.…”
Section: Resultsmentioning
confidence: 99%
“…Filopodia are indispensable for neuritic initiation (Dent et al. 2007; Flynn 2013). The actin‐based filopodia first protrude, then MT follow the lead of the advancing filopodia that finally become elongating neurites.…”
Section: Discussionmentioning
confidence: 99%